Deciphering Neolithic activities from a Cardial burial site (Cova Bonica) on the western Mediterranean coast - Daura, Joan (2019)
Cova Bonica has yielded one of the few assemblages of Cardial Neolithic records of directly dated human remains (c. 5470 and 5220 years cal. BC – unmodelled) in the Iberian Peninsula and has provided the first complete genome of an Iberian farmer. A minimum of seven individuals and six age clusters have been ascribed on the basis of the disarticulated human bones. A large number of archaeological artifacts have likewise been identified in the same layer, preserved in a small number of remnants in different areas of the cave. This study presents the results of a multi-proxy archaeological analysis of the spatial distribution, human remains, small and large mammals, palaeobotanical remains, lithics, ceramics and radiocarbon dating, with the aim of reconstructing the cave's history and the context of the layer containing the human remains. The results suggest the cave was used for at least two distinct purposes: one related to its use for funerary practices, as documented by a small group of artifacts (ornamental objects, ceramics, tools), charcoal and small mammals; the other related to its use as a sheep pen as indicated by reworked fumier, the results of a zooarchaeological study and an ovicaprine palaeodemographic profile. The paper concludes that the funerary and ritualistic practices of the Cardial Neolithic in SW Europe are difficult to reconstruct because human remains are often scattered in archaeological layers where other human activities may also have been conducted. For this reason, artifacts associated with human remains do not constitute a solid foundation on which to reconstruct funerary practices. Indeed, only a multi-proxy analysis of the archaeological material is capable of evaluating different geological and/or archaeological processes and their associated activities.